Neutralność podatkowa importu i eksportu kapitału a harmonizacja podatku dochodowego od osób prawnych - Uchman, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents some problems connected with tax neutrality of corporate tax. The author draws attention to certain solutions and changes which could (at least partially) make the tax regulations more neutral. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 200-207